Daya Hidup Spermatozoa Epididimis Sapi Persilangan yang Dipreservasi dengan Air Kelapa Muda pada Suhu 5oC (VIABILITY OF EPIDIDYMAL SPERMATOZOA CROSSBREED CATTLE PRESERVED WITH COCONUT WATER AT 5oC) - Rizal, Muhammad; Riyadhi, Muhammad; Irawan, Bambang; Wahdi, Anis; Habibah, Habibah; Herdis, Herdis (Jurnal Veteriner, 2018)
The objective of this research was to examine the effectiveness of coconut water with various egg yolk concentrations in maintaining the viability of epididymal spermatozoa of crossbreed cattle preserved at 5oC. Five testis with epididymides of crossbreed cattle were obtained from slaughterhouse. Epididymal spermatozoa was collected by the combination of slicing, flushing and tissues pressure methods of cauda epididymides with saline solution (0.9% NaCl). Collected-spermatozoa was equally divided in volume into four tubes and diluted with lactose extender containing 20% egg yolk (control), 90% coconut water + 10% egg yolk (CWEY10), 85% coconut water + 15% egg yolk (CWEY15), and 80% coconut water + 20% egg yolk (CWEY20), repectively. Diluted-spermatozoa was stored in refrigerator at 5oC. Quality of dilutedspermatozoa including percentages of motile spermatozoa (MS), live spermatozoa (LS), spermatozoa with intact plasma membrane (IPM) were evaluated every day during four days of storage. Data were analyzed by using completely randomized design with four treatments and five replicates. Means were compared with significant difference test at 0.05 significant level. Results of this study showed that mean of spermatozoa concentration, percentage of MS, percentage of LS, percentage of spermatozoa abnormal, and percentage of IPM of crossbreed cattle fresh epididymal spermatozoa were 1,414 million cell/ml, 72%, 85%, 9%, and 90%, respectively. At day-4 of the storage, percentages of MS, LS, and IPM of control (43, 52.2, 59.2%) and CWEY20 (42, 52, 59%) were significantly (P<0.05) higher than CWEY10 (33, 45.4, 52.8%) and CWEY15 (37, 50, 54.6%). In conclusion, lactose and CWEY20 extenders could be maintaining the quality of epidydimal spermatozoa of crossbreed cattle for three days preservation at 5oC and two days for CWEY10 and CWEY15.